A Highly Sensitive, Direct X‐Ray Detector Based on a Low‐Voltage Organic Field‐Effect Transistor. (4th July 2017) - Lai, Stefano; Cosseddu, Piero; Basiricò, Laura; Ciavatti, Andrea; Fraboni, Beatrice; Bonfiglio, Annalisa
Abstract : A novel organic transistor‐based sensor for direct X‐ray detection is proposed. The device operates at low voltages (≤3 V) and is entirely fabricated on flexible, plastic substrates with techniques that can be easily upscaled to an industrial scale. It is claimed that flexible, low voltage organic transistors have never been employed as direct ionizing radiation detectors, as two terminal photodetectors are typically considered for this application. It is demonstrated that, differently from two‐terminal photodetectors, X‐ray detection ability of the proposed sensor can be tuned acting on the transistor polarization conditions. Thanks to such a peculiar feature of the device, outstanding values of sensitivity are observed (up to 1200 nC Gy −1 ), much larger than the ones reported for two terminal direct organic photodetectors. It is notable that, the reported performances have been obtained using as sensing layer a standard, commercially available organic semiconductor: a complete explanation of the mechanism behind the detection ability is thoroughly discussed. The device functionality is perfectly maintained even after the exposure to high X‐ray doses (160 Gy), thus demonstrating the significant radiation hardness of the detector. Abstract : A low‐voltage, organic‐transistor‐based X‐ray sensor fabricated on flexible, plastic substrate is reported. Remarkable sensitivity values are demonstrated. The detection ability of the device is reliant on the transistor operating regime, thus allowing a precise tuning of its sensitivity. A good radiation hardness to prolonged X‐ray exposure is also demonstrated.